The Influence of the Use of Interactive Media in Islamic Religious Education Learning on Students' Learning Interests at SMP Negeri 2 Sipispis - Nuruddin, Ahmad; Purba, Yusnar; Khairuddin; Maya; Sarti (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2024)
This study aims to examine the effect of using interactive media in Islamic Religious Education (PAI) learning on students' learning interest at SMP Negeri 2 Sipispis. The background of this study is based on the low interest in learning of students as reflected in the lack of active participation and enthusiasm in participating in PAI learning. The use of interactive media is expected to be a solution to overcome this challenge and create a more interesting learning atmosphere. This study uses a quantitative method with an experimental approach. Data were collected through questionnaires, observations, and interviews to measure the level of students' learning interest before and after the use of interactive media. The research sample involved grade VIII students who were selected randomly. Data analysis was carried out using statistical tests to see significant differences between conditions before and after the intervention. The results showed that the use of interactive media, such as learning videos, online quizzes, and material simulations, significantly increased students' learning interest. This increase can be seen from the increasing activity of students in discussions, increasing curiosity, and the ease of students in understanding teaching materials. These findings indicate that the integration of technology in PAI learning can strengthen students' intrinsic motivation and support a more meaningful learning process. Therefore, it is recommended for teachers to continue to develop technology-based learning innovations in order to create a conducive learning environment that is in accordance with the characteristics of the current digital generation